Design and implementation of power and area optimized AES architecture on FPGA for IoT application - P, Rajasekar; H, Mangalam (Circuit world, 2021)
Purpose The growing trends in the usage of hand held devices necessitate the need to design them with low power consumption and less area design. Besides, information security is gaining enormous importance in information transmission and data storage technology. In addition, today’s technology world is connected, communicated and controlled via the Internet of Things (IoT). In many applications, the most standard and widely used cryptography algorithm for providing security is Advanced Encryption Standard (AES). This paper aims to design an efficient model of AES cryptography for low power and less area. Design/methodology/approach First, the main issues related to less area and low power consumption in the AES encryption core are addressed. To implement optimized AES core, the authors proposed optimized multiplicative inverse, affine transforms and Xtime multipliers functions, which are the core function of AES’s core. In addition, to achieve the high throughput, it uses the multistage pipeline and resource reuse architectures for SBox and Mixcolumn of AES. Findings The results of optimized AES architecture have revealed that the multistage pipe line and resource sharing are optimal design model in Field Programmable Gate Array (FPGA) implementation. It could provide high security with low power and area for IoT and wireless sensors networks. Originality/value This proposed optimized modified architecture has been implemented in FPGA to calculate the power, area and delay parameters. This multistage pipeline and resource sharing have promised to minimize the area and power.